The Port of Missing Men - Nicholson, Meredith, 1866-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Port of Missing Men" by Meredith Nicholson is a novel likely written in the early 20th century. The story combines elements of mystery and adventure, centering on the character John Armitage, an enigmatic figure with a past intertwined with European nobility. The opening of the book introduces readers to John Armitage as he engages in a dialogue with Count Ferdinand von Stroebel, an aging Austrian premier. Their conversation hints at political intrigue and dark secrets surrounding the death of Archduke Karl, suggesting that Armitage holds crucial information about the events unfolding in Europe. The narrative unfolds in Geneva, where tension builds as Armitage navigates the complexities of espionage, deception, and personal connections, making clear that both his life and the fate of the empire are at stake. This opening sets the stage for a suspenseful exploration of identity, loyalty, and the impact of past choices on present circumstances. (This is an automatically generated summary.)
Release date is 2004-11-01
E-text prepared by Audrey Longhurst, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team. HTML and images added by Rick Tonsing.
Keywords: Fiction